2017
DOI: 10.11604/pamj.2017.28.90.11054
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcome of acute kidney injury among Sudanese adults admitted to a tertiary level hospital: a retrospective cohort study

Abstract: IntroductionLittle is known about the pattern and outcome of Acute Kidney injury (AKI) in Sudan. This study aimed to determine the etiology and outcome of AKI among Sudanese adults.MethodsA retrospective cohort study was conducted in a tertiary level hospital, Soba University Hospital, Sudan. The medical records of all adults admitted to hospital from the 1st of January to 31st of December 2014 were reviewed. The diagnosis and severity of AKI was defined as per the Kidney Disease Improving Global Outcomes (KDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
6
20
1
Order By: Relevance
“…Marwa et al [15]; have conducted a large retrospective cohort (6769 hospitalized subjects), a 1 year study in a tertiary teaching hospital (Soba University hospital) at Khartoum, Sudan. The incidence of AKI in this study was 5.7% compared to 39.0% in our study and the mortality rate was 31.2% compared to 87.8% in our study.…”
Section: Comparison Between the Findings Of The Current Study And Othmentioning
confidence: 99%
See 1 more Smart Citation
“…Marwa et al [15]; have conducted a large retrospective cohort (6769 hospitalized subjects), a 1 year study in a tertiary teaching hospital (Soba University hospital) at Khartoum, Sudan. The incidence of AKI in this study was 5.7% compared to 39.0% in our study and the mortality rate was 31.2% compared to 87.8% in our study.…”
Section: Comparison Between the Findings Of The Current Study And Othmentioning
confidence: 99%
“…The incidence of AKI in this study was 5.7% compared to 39.0% in our study and the mortality rate was 31.2% compared to 87.8% in our study. The large variations between the two studies may be attributed to the variations in the study design (the retrospective vs. prospective), the quality of care, and differences between the two settings from where data was generated (versus all hospital wards versus ICU) [15].…”
Section: Comparison Between the Findings Of The Current Study And Othmentioning
confidence: 99%
“…There was no statistical association between age group and duration of disease among respondents (P-value = 0.243) ( Table 1). Looking at Table 2 we noticed that the duration of the disease among the different duration of disease group is higher among male compare to female except among the group (16)(17)(18) years. There was no statistical association between the duration of the disease and the gender of the respondents.…”
Section: Resultsmentioning
confidence: 94%
“…In Sudan, it is reported that the age is directly proportion to the requirement of dialysis. Also mortality is significantly related to increase in patient's age, plus other health problems [16]. Another study carried out in Sudan revealed that the mean age of ESRD Patients is 49 ± 15.8 (years) and 63.4% are male and 76.3% are unemployed.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Osman M et al, was also not dissimilar with our study as they found volume depletion, other than being common cause was also a significant predictor of mortality in AKI patients. 11 Sepsis pertained to be the commonest of causes for AKI (44.3%) and an independent predictor of mortality in AKI patients. One study have supported this finding and the results were not dissimilar.…”
Section: Discussionmentioning
confidence: 95%